PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Habibah, Binti Nur; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze and to test value added capital employed, value added human capital, and structural capital value added to the financial performance. The independent variables which are used in this research are value added human capital, value added capital employed, and structural capital value added and the dependent variable is financial performance. The samples are 10 Food and Beverages companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2014 periods. The sample collection has been done by using purposive sampling method. The data has been retrieved from the annual report of manufacturing companies on consumer goods sector which are listed in Indonesia Stock Exchange. The hypothesis test data has been done by using multiple linear regressions analysis data. The result of this research shows that value added capital, value added capital employed and structural capital value added have positive and significant influence to the financial performance.Keywords: Value Added Capital Employed, Value Added Human Capoital, Structural Capital Value Added, Financial Performance.